PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATA KULIAH TATA HIDANG - Haryanto, Haryanto; Mulyatiningsih, Endang; E, Prihastuti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The goal of this research in research & design on technology is to produce video learning media prototype needed for "Tata Hidang" (table set-up) practicum in Home Economics, Food Management study program, Faculty of Engineering. The media production design consists of two parts: the subject matter design and the video interactive program design.The subject matter design and video interactive program design in clude matters related to steps of selecting and writing the goals of the spe cial purpose program design, selecting and organizing program contents, making storyboard, evaluating storyboard by experts and students, making revision based on the results and comments from the evaluation of the storyboard, making detailed scripts based on the completed storyboard, evaluating and revising the scripts, making the product ready, taking the pic tures and making adjustments, and picture editing. Based on the subject matter and audio-video data, interactive learning media were produced. There are four steps, i.e., 1) Setting requirements for analysis system, 2) De signing software system (algorithms, Data Flow Diagram, flow chart), 3) Implementing the Coding, and 4) Evaluating software system. Black box testing was needed to evaluate the product. There are observations on out puts (user interface) to treat parts of the input regardless of the process. In ternal product validity (by the researcher) and external validity (by expert) were tested to insure the software quality.The result obtained is Video Cassette Display of interactive learningmedia software for "Tata Hidang" practicum. The findings of the research are: 1) the software was running well based on internal validity. 2) the ex ternal validity of the software can be presented as follows: competence mat ter (81,82%), sub-competence coverage (82,95%), media page running (81,98%), video playing (83,77%), and audio hearing (80,36%). Based on these findings the software product for "Tata Hidang" course can be used properly. Key words: learning media, interactive video, tata hidang